Pengaruh Hypnobreastfeeding dan Pijat Laktasi Terhadap Produksi ASI - Franciska, Yunetra; Yuka, Aprillia Ayu Shinta (jitek, 2023)
Mother's milk's nutritional content shields the infant's immune system, allowing for healthy growth and development. Because breastfeeding has positive health effects for both mother and child, it is strongly advised during the early stages of pregnancy. The truth of the matter is that a lot of mothers still struggle to exclusively breastfeed their children for the whole six months. Hypnobreastfeeding and lactation massage are two strategies that can help people who want to exclusively breastfeed get past their obstacles. This study sought to ascertain the impact of lactation massage and hypnobreastfeeding on breastfeeding mothers' ability to produce milk in the independent Palembang midwife's practice. The design of this study was a quasy experimental design with a pre-test post-test control group design technique in which 60 postpartum mothers were divided into two groups. The intervention group (n = 30) underwent hypnobreastfeeding and lactation massage as a sort of therapy and continued with measurements of breast milk and the control group (n = 30) did not receive any treatment or intervention. Questionnaires, checklists, guides for using hypnobreastfeeding and lactation massage, as well as breast pumps to measure milk supply, were the devices employed. With asymptotic statistical values, the results demonstrated that the delivery of hypnobreastfeeding therapy and lactation massage in the intervention group compared to the control group had a significant impact on milk production. Sig. (2-tailed) = 0.001, and the average increase in milk production between the intervention group and the control group was 25.03 ml compared to 8.56 ml.